2019
DOI: 10.1021/acs.macromol.9b01697
|View full text |Cite
|
Sign up to set email alerts
|

Branched Polyethylene as a Plasticizing Additive to Modulate the Mechanical Properties of π-Conjugated Polymers

Abstract: A new approach for improving the mechanical properties of semiconducting polymers was established via physical combination of a diketopyrrolopyrrole-based conjugated polymer with a low-molecularweight branched polyethylene (BPE). The influence of the BPE additive on the stretchability and mechanical properties of the conjugated polymer was studied at different scales, using various characterization techniques, including atomic force microscopy, UV−vis spectroscopy, and grazing incidence X-ray diffraction. At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…[21,22] Notably, previous studies of BPE in organic electronics showed that utilization of BPE as an additive for the solution processing of semiconducting polymers can significantly impact the optoelectronic and thermomechanical properties of semiconducting polymers. [23,24] However, in these previous examples, processing of the semiconducting polymers with toxic chlorinated solvent was critical and still required. While the amount of chlorinated solvents is negligible when spincoating is used for processing, solutions prepared from as low as 2 wt% of chlorinated solvents can be significantly challenging to use at large-scale due to toxicity and high boiling point.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] Notably, previous studies of BPE in organic electronics showed that utilization of BPE as an additive for the solution processing of semiconducting polymers can significantly impact the optoelectronic and thermomechanical properties of semiconducting polymers. [23,24] However, in these previous examples, processing of the semiconducting polymers with toxic chlorinated solvent was critical and still required. While the amount of chlorinated solvents is negligible when spincoating is used for processing, solutions prepared from as low as 2 wt% of chlorinated solvents can be significantly challenging to use at large-scale due to toxicity and high boiling point.…”
Section: Introductionmentioning
confidence: 99%
“…(Figure 8(A)) Thus, it is vital to establish the structure‐thermal/mechanical property relationship of semiconducting polymer thin films for the design of next‐generation stretchable CPs. In the past decade, two primary strategies have been applied to tune the mechanical response of CPs: molecular engineering, including regioregularity, molecular weight, and backbone/side‐chain engineering; as well as postmodification, including cross‐linking, physical blending, and etc 20,69,119,120,124–132 . In this section, we briefly summarized the past efforts along this line to highlight the scientific significance of water‐assisted tensile tests.…”
Section: Applications Of Water‐assisted Tensile Testsmentioning
confidence: 99%
“…In the past decade, two primary strategies have been applied to tune the mechanical response of CPs: molecular engineering, including regioregularity, molecular weight, and backbone/side-chain engineering; as well as postmodification, including cross-linking, physical blending, and etc. 20,69,119,120,[124][125][126][127][128][129][130][131][132] In this section, we briefly summarized the past efforts along this line to highlight the scientific significance of water-assisted tensile tests. The mechanical property of representative semiconducting polymers was also listed in Table 1.…”
Section: Applications Of Water-assisted Tensile Testsmentioning
confidence: 99%
“…In a second approach, we utilize a physical blending approach whereby an elastomer is composited with the BHJ as an effective approach to mechanically soften the photoactive layer. 27,29,30,36,37 For the first time to our knowledge, we successfully implement elastomers as plasticizer components into photoactive BHJ layer of OPV devices. Unlike bis-azide molecules, which covalently bond to two PC 61 BM molecules, requires chemical specificity and treatment such as thermal annealing, the elastomer does not covalently bond with any BHJ component.…”
Section: Introductionmentioning
confidence: 99%